2007
DOI: 10.1016/j.jpeds.2006.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin Prophylaxis for Preterm Infants: The Impact of 2 Multicentered Randomized Controlled Trials on Clinical Practice

Abstract: Objectives-Two multicentered RCTs in premature infants TIPP, 2001) found beneficial effects of indomethacin prophylaxis on the incidences of patent ductus arteriosus (PDA), PDA ligation, and severe intracranial hemorrhage (ICH). The Ment-trial recommended its use. The TIPP-trial failed to find a benefit in its primary outcome (improved survival/ neurodevelopmental outcome). This negative result may have discouraged prophylactic indomethacin use.Study Design-We used the NICHD Neonatal Network Registry to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
1
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 31 publications
0
59
1
4
Order By: Relevance
“…16,29 In contrast, sepsis represents a partially preventable disease. Studies in adults, children, and neonates have shown that institutional protocols, such as care bundles, if applied correctly, can significantly reduce nosocomial infections.…”
Section: Discussionmentioning
confidence: 99%
“…16,29 In contrast, sepsis represents a partially preventable disease. Studies in adults, children, and neonates have shown that institutional protocols, such as care bundles, if applied correctly, can significantly reduce nosocomial infections.…”
Section: Discussionmentioning
confidence: 99%
“…However a consistent lack of demonstrable improvement in neonatal and neurodevelopmental outcomes has sparked an existential debate regarding the role of ductal closure therapies in the neonatal intensive care unit 3 23. Trials of pharmacological agents have demonstrated improved PDA closure rates and a decrease in symptomatic PDA and surgical ligation, though they were conducted within a clinical practice paradigm of early diagnosis and treatment.…”
Section: Pda Treatment: Reflections Of the Past 10 Yearsmentioning
confidence: 99%
“…The reason for the lack of long-term beneficial effects despite a decrease in the incidence of severe IVH is not clear, but has, among others, been attributed to an excessively large anticipated effect size. 34 The third reason for the controversy is that the medications most commonly used to close the PDA are not without significant side effects. Fortunately, the adverse renal side effects and inhibition of platelet aggregation are, in the vast majority of the cases, transient.…”
Section: Introductionmentioning
confidence: 99%